Greywater Treatment Using Modified Pvdf Membrane - Goh, Jian Loon (Universiti Sains Malaysia, 2022)
Lignin is a sustainable substance which can be extracted from a wide range of lignocellulosic biowastes in Malaysia. It can be blended into PVDF membranes to enhance the membrane morphology for oil-water filtration. PVDF polymeric matrix membrane is superb in terms of chemical and thermal stabilities, which make it very promising to be utilised as a membrane matrix for water separation. However, poor hydrophilic property of the PVDF has led to the severe fouling during operation. Thus, current work is performed to increase the surface hydrophilicity and change surface roughness of the membrane which could reduce membrane fouling and reduce the extent of permeate flux decline. Lignin dissolved in sodium hydroxide solution can be coated with calcium carbonate to improve the surface hydrophilicity which correlate the membrane fouling and change the surface roughness of the membrane which correlate the flux decline. In this work, the polyvinylidene fluoride (PVDF) membrane was coated with lignin and calcium carbonate to improve the filtration of oil water emulsion. 0.75wt. % lignin dissolved in 0.5wt. % sodium hydroxide solution with varied calcium carbonate concentration (1wt. %, 3wt. % and 5wt. %). Surface modification permits the enhancement of membrane properties without affecting the existing membrane formulation. Membrane characterizations were performed using contact angle goniometer, RS Weight and UV-vis spectrophotometer to determine the water contact angle, permeate flux and percent of oil rejection respectively.